2011
DOI: 10.1073/pnas.1016653108
|View full text |Cite
|
Sign up to set email alerts
|

Quantum nature of the hydrogen bond

Abstract: Hydrogen bonds are weak, generally intermolecular bonds, which hold much of soft matter together as well as the condensed phases of water, network liquids, and many ferroelectric crystals. The small mass of hydrogen means that they are inherently quantum mechanical in nature, and effects such as zero-point motion and tunneling must be considered, though all too often these effects are not considered. As a prominent example, a clear picture for the impact of quantum nuclear effects on the strength of hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
382
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 398 publications
(406 citation statements)
references
References 45 publications
22
382
2
Order By: Relevance
“…4e,f), was likewise similar in energy to the adsorbed C 3 and C s hexamers; although unstable in the gas-phase calculation (it converged to the S 6 structure), on hydroxylated FeO the adsorption energy was calculated as À 0.67 eV per H 2 O. Although the differences in energy between these configurations are too small to predict which will be dominant in experimentally-observable H 2 O clusters 40,41 , it is clear that the hydroxylated FeO surface significantly stabilizes bonding configurations that otherwise are unfavourable. This very likely leads to a significantly greater degree of proton disorder than would be expected based on gas-phase results.…”
Section: Resultsmentioning
confidence: 79%
“…4e,f), was likewise similar in energy to the adsorbed C 3 and C s hexamers; although unstable in the gas-phase calculation (it converged to the S 6 structure), on hydroxylated FeO the adsorption energy was calculated as À 0.67 eV per H 2 O. Although the differences in energy between these configurations are too small to predict which will be dominant in experimentally-observable H 2 O clusters 40,41 , it is clear that the hydroxylated FeO surface significantly stabilizes bonding configurations that otherwise are unfavourable. This very likely leads to a significantly greater degree of proton disorder than would be expected based on gas-phase results.…”
Section: Resultsmentioning
confidence: 79%
“…Computations indicated that the interface can be stabilized by a network of interphase hydrogen bonding between FAP and gypsum, suggesting that hydrogen bonding plays an important role in providing binding strength at the interface. The computations, which are based on the density functional theory whose capabilities have been used extensively to predict H-bonding network 39,40 , also show that the hydrogen bond network is mediated through the gypsum water molecules, suggesting that the hydration state of sulphate plays a specific stabilization role at the interface. To compare the influence of fluoride ions on interface stability, we computed the bond length and bond energies of both FAP/CAS and HAP/ CAS interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…the protons participating in H-bonds, as well as the static properties of ice and water, with the quantal behavior originating from zero-point motion. It has been recently suggested that a detailed description of the strength of the hydrogen bond is a prerequisite to elucidate the influence of quantum nuclear effects on the hydrogen bonding [1]. The picture proposed is that this effect arises from a competition between anharmonic quantum fluctuations of intermolecular bond bending and intramolecular covalent bond stretching, where the latter fluctuations tend to strengthen H-bonds whereas the former to weaken H-bonds.…”
Section: Introductionmentioning
confidence: 99%